0645 The Association of Hypoglossal Nerve Stimulator Adherence and Insomnia. (27th May 2020) - Sharma, M; Chacko, A; Rosenthal, M; Khan, M
Abstract: Introduction: The gold standard for treatment of Obstructive sleep apnea (OSA) is continuous positive airway pressure (CPAP). However, CPAP adherence is less than 50%. An alternative treatment is the hypoglossal nerve stimulator (HNS) which displaces the tongue anteriorly to treat upper airway obstruction. Difficulties tolerating HNS are related to stimulation discomfort. In this study, we investigated insomnia as a barrier to adherence. Methods: Patients implanted and activated with HNS at The Ohio State University Wexner Medical Center between 2015 and 2019 were eligible. Patient usage data from the previous six months was obtained and subjects were asked to complete an Insomnia Severity Index (ISI). Participants were divided into adherent (defined as use ≥28 hours/week) and non-adherent (use <28 hours/week). Results: 32 subjects were enrolled, 22 in the adherent group and 10 in the non-adherent group. There was a significant decrease in mean treatment AHI in both groups: 36.25 to 11.14 in the adherent group and 36.30 to 15.69 in the non-adherent group (p<0.0001). The mean ISI score in the adherent group was 6.84 which is consistent with no clinically significant insomnia and 8.67 in the non-adherent group consistent with subthreshold insomnia. However, there was not a statistically significant difference between the two groups (p=0.441). There was a statistically significant higher score for the question "Do you worry about your sleep problems?" in the non-adherent group (1.78, SD1.39 vs 0.74. SD 0.81) (p =0.018). Conclusion: This study suggests that patients who have difficulty with sleep may have more difficulty with HNS adherence than those who do not. In particular the question stating "Do you worry about your sleep problems" had a statistically higher score in the non-adherent group. Prospective studies are needed to further explore a possible relationship between insomnia and HNS adherence. Support: N/A